Asymmetric lamb wave propagation and mode isolation in thin plate with spatiotemporal periodic stiffness - Zhao, Liuxian (2019)
The Lamb wave propagation through a thin plate with periodic spatiotemporal variation of material property was investigated through numerical simulations. It was found that regular oscillations of Young's modulus in both space and time can lead to the creation of distinct band gaps for different modes of Lamb wave. Moreover, the dispersion relation for each mode was dependent on the direction of wave propagation (i.e., nonreciprocal). These results allow the Lamb wave modes to be reduced to a single mode traveling in a single direction for specific frequencies. This frequency range was observed to widen with an increasing modulation amplitude of Young's modulus but was not significantly altered by the modulation frequency. The insights derived from this study indicate that spatiotemporal control of material property can be used to effectively isolate Lamb wave modes and reduce reflections, leading to an improvement in the accuracy of the structural health monitoring of materials.